Penerapan Interpretasi Standar Akuntansi Keuangan (ISAK 35) dan Pengembangan Sumber Daya Manusia (SDM) sebagai Upaya Peningkatan Akuntabilitas Dana Masjid Nidaaul Khoirot Semarang - Taufiq Andre Setiyono; Khoirul Attiq; Grace Tianna Solovida; Evita Sulistyowati; Wahyu Anindya Tri Hapsari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
Based on the results of the condition situation analysis, to make financial reports according to standards, not only guidelines such as financial accounting standards are needed, but it is also necessary to have resources that have adequate abilities and understanding. The main problem faced by the current Nidaaul Khoirot Mosque manager is that the Mosque only records cash in and cash out, does not record the invetarization of assets owned so that the economic value of the Mosque cannot be known. So, to overcome these problems, the purpose of this novice community empowerment is to assist the mosque management of the Mosque in the application of ISAK 35 and the development of Mosque resources as an effort to increase the accountability of Mosque funds and management.